Enhanced pain modulation capacity among individuals with borderline personality disorder: A possible mechanism underlying their hypoalgesia. (28th November 2019) - Defrin, Ruth; Cohen Sagy, Nitzan; Biran, Iftah; Goor‐Aryeh, Itay; Shai, Roni; Ginzburg, Karni
Abstract: Background: Ample evidence suggests that individuals with borderline personality disorder (BPD) exhibit hyposensitivity to pain. Since the underlying mechanism of the pain hyposensitivity is unknown, we tested here for the first time whether this hyposensitivity is pain specific or exists also for innocuous sensation, and whether it is associated with enhanced descending pain modulation capabilities. Methods: Participants were 55 women; 22 patients with BPD and 33 matched healthy controls. Testing included the measurement of warmth sensation threshold (WST), heat‐pain threshold (HPT), pain adaptation, conditioned pain modulation (CPM) and temporal summation of heat‐pain (TSP). The level of dissociation was also evaluated. Results: Women with BPD had higher WST and HPT compared with healthy controls. Moreover, women with BPD had greater magnitude of pain adaptation and CPM as well as higher dissociation level compared to controls. In neither the BPD nor the control group did WST and HPT correlate with pain adaptation, CPM or dissociation. In the BPD group only, HPT inversely correlated with the magnitude of TSP. Conclusions: Women with BPD present generalized hyposensitivity to both innocuous and noxious stimuli. Furthermore, women with BPD exhibit more efficient pain inhibition capabilities than healthy controls. While efficient pain modulation may underlie pain hyposensitivity in BPD, both traits may exist independently from each other, or may be moderated by another factor such as dissociation. Significance: On the basis of testing pronociceptive and antinociceptive components among individuals with BPD and healthy controls, this study reveals enhanced ability to inhibit pain among woman with borderline personality disorder (BPD) which may underlie hyposensitivity to both noxious and innocuous stimuli and perhaps also self‐injurious behaviour among these individuals. The study contributes novel information on possible mechanisms involved in BPD manifestations.